MODULATION OF PLASMODIUM FALCIPARUM CIRCUMSPOROZOITE PROTEIN GENE EXPRESSION BY ANTIBODIES - C Cassandra (International Journal of Medical Science and Public Health Research, 2024)
The Plasmodium falciparum circumsporozoite protein (CSP) is a crucial antigen expressed during the sporozoite stage of the malaria parasite’s lifecycle and is a key target for vaccine development. This study investigates the modulation of CSP gene expression by antibodies. We examined how specific antibodies influence CSP gene transcription and translation using in vitro assays with P. falciparum sporozoites and a recombinant CSP expression system. Our findings reveal that antibodies can significantly alter CSP gene expression, both upregulating and downregulating its production depending on their specificity and concentration. This modulation suggests that antibody-mediated immune responses could impact the efficacy of CSP-based vaccines and the overall immune response to malaria infection. These results provide insights into the potential mechanisms through which antibodies affect parasite antigen expression and highlight considerations for designing effective malaria vaccines.